New research on the Middle Paleolithic of the Middle Prut Basin - Vishnyatsky, L.; Burlacu, V. (Materiale și Cercetări Arheologice, 2021)
In 2015– 2017 the Prut-Dniester expedition from the Institute for the History of Material Culture of the Russian Academy of Sciences carried out field research at a number of Paleolithic localities in the middle reaches of the Prut and Dniester in the north-west of Moldova. This paper presents the results of new research at the Middle Paleolithic open air site of Teţcani X and the cave site of Buzdujeni I. The cultural layer of Teţcani X yielded a representative collection of flint artifacts. The flaking technology is oriented on the production of points, which were struck from unifacial single platform cores. The tool set is typical of Mousterian, no bifaces are present. The cave of Buzdujeni I was nearly completely excavated by N. A. Chetraru in the 1970’ s, but remained largely unpublished. The re-analysis of the old collection together with the materials obtained by us in 2017 challenges the once popular idea that the industry of Buzdujeni I belongs to Denticulate Mousterian, highlighting instead its Micoquian affinities such as presence of various bifacial tools. The available biostratigraphic and radiometric data, including newly obtained radiocarbon dates, appears to suggest that both sites can be broadly dated to the first half of MIS-3 or to MIS-4, with Teţcani X being probably somewhat older than Buzdujeni I